2015
DOI: 10.4236/aim.2015.51005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bioproducts on Mycorrhizal Occurrence and Diversity in the Rhizosphere of Strawberry Plants under Controlled Conditions

Abstract: The new products obtained from natural resources are an alternative to methods based on traditional mineral fertilizers, which are destructive for soil mycorrhizal communities. Our experiment was carried out to evaluate the effect of organic fertilizers and amendments of very diverse composition on mycorrhizal abundance and diversity, as well as on root growth, in strawberry plants cv. "Honeoye". The plants were grown in rhizoboxes filled with a podsolic soil. The plants were treated with granulated bovine man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…The effectiveness of mycorrhiza was also negligible when vermiculite (Humus UP) was used as a fertilizer. On the other hand, in the presence of manure or biopreparations such as BF Amin or Vinassa, stimulation of growth of young trees under the influence of mycorrhiza was clearly evident, which is consistent with previous studies conducted by Grzyb et al [13,21] and Sas Paszt et al [2]. Mycorrhization had no effect on the growth of sour cherry maidens in the presence of the fertilizer Florovit Eko.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The effectiveness of mycorrhiza was also negligible when vermiculite (Humus UP) was used as a fertilizer. On the other hand, in the presence of manure or biopreparations such as BF Amin or Vinassa, stimulation of growth of young trees under the influence of mycorrhiza was clearly evident, which is consistent with previous studies conducted by Grzyb et al [13,21] and Sas Paszt et al [2]. Mycorrhization had no effect on the growth of sour cherry maidens in the presence of the fertilizer Florovit Eko.…”
Section: Discussionsupporting
confidence: 82%
“…This effect had been confirmed by previous studies carried out at the Research Institute of Horticulture in Skierniewice. Sas Paszt et al [2] showed negative effects of NPK fertilization on the formation of mycorrhizas on the roots of fruit plants and the reduction in biodiversity and populations of beneficial soil microflora. Thus the low effectiveness of mycorrhiza is caused by the negative effect of NPK fertilization on the development of soil microflora and by the sufficient availability of NPK minerals under mineral fertilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations